Nazrul : an evaluation - Huda, Muhammad Nurul (Dhaka : Nazrul Institute, 1997)
Contributed articles on the works of Kazi Nazrul Islam, 1899-1976, Bengali poet.
Keywords: Nazrul Islam, -- Kazi, -- 1899-1976 -- Criticism and interpretation